PELATIHAN PENULISAN SURAT DINAS DI PEKON BANYU URIP - Dwi Fitriyani (Universitas Muhammadiyah Pringsewu, 2017)
Dedication to society in Banyu Urip village was conducted for the village staff. It is required due to the fact that many mistakes in writing official letter. This service was conducted for giving good alteration and giving knowledge of official letter. The mistake happened because of lack knowledge about the role of writing good formal letter and the unappropriate of eduaction qualification. The service result shows that staff’ knowledge about writing formal letter improve. The letters sent are already appropriate with the role system of formal letter. Keywords: Training, Writing, Formal Letter